Re-energising Europe's global green reach - Giovanni Sgaravatti; Simone Tagliapietra; Cecilia Trasi (Bruegel, 2024)
It will be impossible to contain the global temperature rise to 1.5 to 2 degrees Celsius above pre-industrial levels unless emerging market and developing economies (EMDEs) decarbonise much more rapidly. This policy brief examines the economic case for advanced-country financial support for replacement of coal with renewable energy sources in EMDEs. Such conditional financial support is necessary in the sense that an exit from coal consistent with keeping the global temperature rise to between 1.5êC and 2êC will not happen without it, desirable from the perspective of the financier countries, and financially feasible. Although the global economic benefits of phasing out coal are very large, the costs of exiting coal generally exceed the benefits to EMDEs. However, the collective economic benefits to advanced countries greatly exceed those costs. These net benefits are positive even for small coalitions of advanced countries (G7 or G7 plus EU). The fiscal costs of financing the coal exit in EMDEs (without China) are modest as a share of G7+EU GDP at about 0.3 percent of GDP per year, assuming public-sector participation in renewable energy investment costs through blended finance of around 25 percent. Although providing climate finance to EMDEs is economically desirable and feasible from the G7 perspective, it is not happening at the necessary scale, partly because of incentives and political-economy challenges. Advanced countries are more likely to be willing to commit financing to climate action outside their borders if they have more control over how this money is spent. Developing countries are reluctant to phase out coal unless sufficiently large financial support is forthcoming for renewable investments that are consistent with their development goals. These problems could be overcome by tying renewable finance to a coal phase-out. Already-existing Just Energy Transition Partnerships with South Africa, Indonesia and Vietnam are prototypes of this approach. They should be scaled up, with sufficient grants to pay for coal closures and the social transition in coal communities, by explicitly conditioning funding on a coal phase-out and through a stronger governance structure to implement these deals.
Keywords: 330; European Green Deal; decarbonisation